Greener, Nonhalogenated Solvent Systems for Highly Efficient Perovskite Solar Cells. Issue 21 (30th April 2018) - Yavari, Mozhgan; Mazloum‐Ardakani, Mohammad; Gholipour, Somayeh; Tavakoli, Mohammad Mahdi; Turren‐Cruz, Silver‐Hamill; Taghavinia, Nima; Grätzel, Michael; Hagfeldt, Anders; Saliba, Michael
Abstract: All current highest efficiency perovskite solar cells (PSCs) use highly toxic, halogenated solvents, such as chlorobenzene (CB) or toluene (TLN), in an antisolvent step or as solvent for the hole transporter material (HTM). A more environmentally friendly antisolvent is highly desirable for decreasing chronic health risk. Here, the efficacy of anisole (ANS), as a greener antisolvent for highest efficiency PSCs, is investigated. The fabrication inside and outside of the glovebox showing high power conversion efficiencies of 19.9% and 15.5%, respectively. Importantly, a fully nonhalogenated solvent system is demonstrated where ANS is used as both the antisolvent and the solvent for the HTM. With this, state‐of‐the‐art efficiencies close to 20.5%, the highest to date without using toxic CB or TLN, are reached. Through scanning electron microscopy, UV–vis, photoluminescence, and X‐ray diffraction, it is shown that ANS results in similar mixed‐ion perovskite films under glovebox atmosphere as CB and TLN. This underlines that ANS is indeed a viable green solvent system for PSCs and should urgently be adopted by labs and companies to avoid systematic health risks for researchers and employees. Abstract : The greener solvent anisole is used for fabrication of solar cells. Here, anisole is used both for quenching the perovskite film and the solvent for the hole transporter material, which provides high photovoltaic performance and a safer work environment with less systematic risk of long‐term health hazards.